2018
DOI: 10.1096/fj.201701415r
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic exploitation of IPSE, a urogenital parasite‐derived host modulatory protein, for chemotherapy‐induced hemorrhagic cystitis

Abstract: Chemotherapy-induced hemorrhagic cystitis (CHC) can be difficult to manage. Prior work suggests that IL-4 alleviates ifosfamide-induced hemorrhagic cystitis (IHC), but systemically administered IL-4 causes significant side effects. We hypothesized that the Schistosoma hematobium homolog of IL-4-inducing principle from Schistosoma mansoni eggs (H-IPSE), would reduce IHC and associated bladder pathology. IPSE binds IgE on basophils and mast cells, triggering IL-4 secretion by these cells. IPSE is also an “infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 74 publications
10
64
0
Order By: Relevance
“…We previously demonstrated that M-IPSE activates basophils in vitro through NF-AT (23). This pathway is implicated in basophil and mast cell expression of IL-4, which we have observed in vivo in mice administered H-IPSE H06 (17). Moreover, we have also noted that ifosfamide-challenged mice given H-IPSE H06 are protected from several pathogenic aspects of hemorrhagic cystitis in an IL-4-dependent fashion (17).…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…We previously demonstrated that M-IPSE activates basophils in vitro through NF-AT (23). This pathway is implicated in basophil and mast cell expression of IL-4, which we have observed in vivo in mice administered H-IPSE H06 (17). Moreover, we have also noted that ifosfamide-challenged mice given H-IPSE H06 are protected from several pathogenic aspects of hemorrhagic cystitis in an IL-4-dependent fashion (17).…”
Section: Resultsmentioning
confidence: 60%
“…This pathway is implicated in basophil and mast cell expression of IL-4, which we have observed in vivo in mice administered H-IPSE H06 (17). Moreover, we have also noted that ifosfamide-challenged mice given H-IPSE H06 are protected from several pathogenic aspects of hemorrhagic cystitis in an IL-4-dependent fashion (17). Thus, we sought to demonstrate that H-IPSE H03 and H-IPSE H06 , which are both S. haematobium orthologs of M-IPSE, also stimulate IL-4-associated reporter gene expression in vitro .…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations